Magic school bus gets baked in a cake : a book about kitchen Chemistry. (New York : Scholastic, 1995)
Learn some kitchen chemistry, when you read this book.
From the episode of the animated TV series produced by Scholastic Entertainment Inc.
Keywords: Kitchen -- Juvenile literature; Children stories